The Viability of an International Financial Services Center in Johannesburg - O’Connell, Geoffrey John (My University, 2011)
The urban decay which has set into the inner city of Johannesburg is compared to the decrepit conditions of the Dublin docklands area in the 1960s. The establishment of the Dublin International Financial Services Centre (IFSC) in the docklands area led to a turnaround with great gains in employment, standard of living and economic upliftment for Ireland. The same benefits are sought for Johannesburg. The report examines numerous IFSCs around the world to establish the key features of an IFSC, how it functions, what its outputs are and what is required to establish one. It then focuses on Dublin as a benchmark for an IFSC and examines what the critical success factors present were. It was found that this has more to do with responsive regulation, human resource quality and high capacity telecommunications infrastructure, than harmful tax regimes and client anonymity. Finally, an area in downtown Johannesburg CBD is ring fenced and its potential to host an IFSC is analysed in some depth. The report contains various cost estimates for the development and estimates the fiscal advantages for the government. It is concluded that it is viable to establish an IFSC in Johannesburg, providing that numerous strategies and facilities are put in place beforehand
MBA thesis - WBS
Keywords: Financial services centres